Role of Circulating MicroRNAs in the Immunopathogenesis of Rejection After Pediatric Lung Transplantation. Issue 10 (October 2017) - Xu, Zhongping; Yang, Wei; Steward, Nancy; Sweet, Stuart C.; Danziger-Isakov, Lara; Heeger, Peter S.; Mohanakumar, Thalachallour
Abstract : Background: Acute rejection (AR) and development of chronic rejection, bronchiolitis obliterans syndrome (BOS) remain major limiting factors for lung transplantation (LTx). This retrospective study is to identify differentially expressed circulating microRNAs (miRNAs) that associate with development of AR and BOS in pediatric lung transplant recipients (LTxR). Methods: We determined the circulating levels of 7 selected candidate miRNAs in 14 LTxR with AR, 7 with BOS, and compared them against 13 stable pediatric LTxR at 1, 6, and 12 months after LTx. In addition, 6 AR, 7 BOS, and 8 stable pediatric LTxR, 16 AR, 17 BOS, and 16 stable adult LTxR were included for validation. Results: MiR-10a, -195, -133b were significantly lower in AR and miR-144, -142-5p, -155 were higher in AR compared to stable ( P < 0.05). In addition, circulating levels of miR-134, -10a, -195, -133b were significantly lower and miR-144, -142-5p, -155 were higher ( P < 0.05) with development of BOS. The receiver-operating characteristic demonstrated that miR-142-5p, miR-155, and miR-195 strongly discriminated patients with AR from stable LTxR ( P < 0.001 for all comparisons): miR-142-5p (area under the curve [AUC], 0.854), miR-155 (AUC, 0.876), and miR-195 (AUC, 0.872). Further, miR-10a, miR-142-5p, miR-144, and miR-155 strongly discriminated BOS from stable LTxR ( P < 0.001 for all comparisons). Conclusions: We demonstrated that differential expression of circulating miRNAs occurs in LTxR with AR and BOS, suggesting that they can provide not only important clues to pathogenesis but also may serve as potential noninvasive biomarkers for AR and BOS after pediatric LTx. Abstract : Xu et al report on the potential of differential expression of circulating miRNAs at discriminating between acute rejection, bronchiolitis obliterans syndrome and stable acceptance in pediatric lung transplant recipients from a multi-institution Clinical Trials in Organ Transplantation in Children study. Supplemental digital content is available in the text.